Review of Biomedical Knowledge and Data Representation with Conceptual Graphs - Volot, F.; Joubert, M.; Fieschi, M. (Methods of Information in Medicine, 1998)
The basis of conceptual graphs theory is an ontology of types of concepts. Concepts issued from the ontology are interlinked by semantic relationships and constitute canonical conceptual graphs. Canonical graphs may be combined to derive new conceptual graphs by means of formation rules. This formalism allows to separate knowledge representation into a conceptual level and a domain-dependent level, and enables to share and reuse a representation. This paper presents conceptual graph applications to biomedical data and concept representation, classification systems, information retrieval, and natural language understanding and processing. A discussion on the unifying role conceptual graphs theory plays in the implementation of knowledge-based systems is also presented.
Keywords: Knowledge Representation; Conceptual Graphs; Information Processing; Classification Systems; Information Retrieval; Natural Language Processing